TINDAK PIDANA DAN PERTANGGUNGJAWABAN PIDANA PENYEBAR VIDEO PORNO MELALUI INTERNET YANG DILAKUKAN INDIVIDU DI INDONESI - ALDILA RENATA (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2018)
Internet is a product of the information Technology Communication is an interactive digital communication network. Internet has both positive and negative impacts. Man makes positive impact towards the information society, which allows every person to obtain and disseminate information quickly, cheaply, and can reach a wide area. One of the few negative impacts the use internet is the dissemination of pornographic video via the internet (cyberporn). In Indonesia and government law enforcement officials still focus on blocking porn websites, porn destroy the product, and focus on the perpetrators only, while the indictment often leads to the propagator (the individual who first spread through internet porn) in the realm of the internet.Keywords : Spreader porn video, Individu, Internet